Sound and Signals - Tohyama, Mikio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This is an up-to-date reference and textbook on modern acoustics from a signal-theoretic point of view, as well as a wave-theoretic approach for students, engineers, and researchers. It provides readers the fundamental basis of acoustics and vibration science and proceeds up to recent hot topics related to acoustic transfer functions and signal analysis including a perceptual point of view. In the first part, the work uniquely introduces into the fundamentals without using heavy mathematics The following, advanced chapters deal with new and deep insights into acoustic signal analysis and investigation of room transfer functions based on the poles and zeros.
Introduction: Scope -- Oscillation and Resonance -- Simple Resonators for Sound -- Propagation of Oscillation -- Vibration of a String and Wave Propagation -- Waves and Speed of Sound in the Air -- Sound in a Tube -- Plane and Spherical Waves -- Sound Waves in Rooms -- Reverberation in Rooms -- Room Transfer Functions -- Sinusoidal Representation of Acoustic Signals -- Mixture of Acoustic Signals -- Diagnostics and Control of Transfer Functions.
Keywords: Engineering; Acoustics; Acoustics in engineering; Engineering; Engineering Acoustics; Acoustics; Signal, Image and Speech Processing